PENURUNAN AKTIVITAS FOSFATASE ASAM Dl DAERAH PERAKARAN BEBERAPA JENIS TANAMAN AKIBAT PERLAKUAN KAPUR DAN LIMBAH INDUSTRI BERTIMAH HITAM - Abdul Kadir Salam; Vivin Vivin; Sri Yusnaini (Jurnal Ilmu Tanah dan Lingkungan, 1999)
Heavy metals are potentially toxic to soil microorganims and are suggested to decrease soil enzymatic activities. Changes in activity of acid phosphatase in root-zones of some tropical plants treated with a lead-containing industrial waste were studied in a glasshouse experiment. Tropical soil sample (from Gedongmeneng and Banjaragung, Lampung) thoroughly treated with an electronics industrial waste at 0 to 40 ton ha·1 and lime at 0 or 5 ton CaC03 ha·1 were cultured with corn (Zea mays L.), amaranth (Amaranthus tricolor L), and green kyllinga (Cyperus kyllinga). Changes in acid phosphatase activity, soil Pb concentration, and soil pH were measured after a 4-week growing period. Soil analysis showed that the activity of acid phosphatase was higher in Banjaragung soil than that in Gedongmeneng soil except in those cultured with green kyllinga. The activity of acid· phosphatase was in general higher in the root-zone of corn than those in the root-zone of amaranth and green kyllinga.The activity of acid phosphatase in both soils decreased with waste addition regardless of plant grown. This was in a good correlation with the increase in soil available Pb as waste was added. However, the decrease in the activity of acid phosphate as the soil pH increased by lime or waste addition suggested that the decrease in the phosphatase activity with waste addition was driven by the increase in soil pH rather than by the increase in the soil available Pb With waste 3dclitton.